2005
DOI: 10.4049/jimmunol.175.10.6509
|View full text |Cite
|
Sign up to set email alerts
|

IL-1β-Mediated Proinflammatory Responses Are Inhibited by Estradiol via Down-Regulation of IL-1 Receptor Type I in Uterine Epithelial Cells

Abstract: The objective of this study was to examine the effects of sex hormones on IL-1β-mediated responses by uterine epithelial cells. The mRNA expression and secretion of human β-defensin-2 and CXCL8 by uterine epithelial cells was examined following stimulation with IL-1β in the presence of estradiol or progesterone. Estradiol inhibited the IL-1β-mediated mRNA expression and secretion of human β-defensin-2 and CXCL8 by uterine epithelial cells while progesterone had no effect. Inhibition of the IL-1β-mediated respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
37
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 81 publications
4
37
2
Order By: Relevance
“…Using the ECC-1 cell line derived from the uterus, we previously showed that IL-1β stimulates mRNA expression and production of HBD2 and IL-8, and that these increases are suppressed by E 2 . 41 We found that E 2 inhibited the expression of IL-1Receptor type I on the ECC-1 epithelial cells. 41 The present studies extend these findings to primary UECs and suggest that E 2 acts by inhibiting IL-1Receptor type I so that cells respond relatively poorly to the IL-1β ligand.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Using the ECC-1 cell line derived from the uterus, we previously showed that IL-1β stimulates mRNA expression and production of HBD2 and IL-8, and that these increases are suppressed by E 2 . 41 We found that E 2 inhibited the expression of IL-1Receptor type I on the ECC-1 epithelial cells. 41 The present studies extend these findings to primary UECs and suggest that E 2 acts by inhibiting IL-1Receptor type I so that cells respond relatively poorly to the IL-1β ligand.…”
Section: Discussionmentioning
confidence: 60%
“…41 We found that E 2 inhibited the expression of IL-1Receptor type I on the ECC-1 epithelial cells. 41 The present studies extend these findings to primary UECs and suggest that E 2 acts by inhibiting IL-1Receptor type I so that cells respond relatively poorly to the IL-1β ligand. Studies are under way to determine whether a similar mechanism exists in primary UECs.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…In this regard, recent studies have demonstrated that physiologic levels of estradiol modulate proinflammatory cytokine production in innate immune effector cells, including epithelial cells and macrophages (12,13). To determine whether estradiol mediates similar effects in primary human monocytes, CD14 ϩ monocytes were preincubated with estradiol at concentrations ranging from 10 Ϫ11 to 10 Ϫ7 M and then stimulated with LPS.…”
Section: Estradiol Attenuates Lps-induced Cxcl8 Production By Primarymentioning
confidence: 99%
“…Recent work from our group has demonstrated that activation of uterine epithelial cells with rIL-1␤ induces expression of the antimicrobial peptide human ␤-defensin 2 (HBD2) (26). Epithelial cells form a first line of defense in the FRT and are in close contact with macrophages.…”
mentioning
confidence: 99%